Sistem Maklumat Murid (SMS) SK Dato' Mohamad Musa - Shahrudin, Ayop; Hasbullah, Seman; Noraini, Fadali; Hamdan, Bujang. (Universiti Malaysia Sarawak (UNIMAS), 2003)
This Sistem Maklumat Murid SK Dato' Mohamad Musa (SMS) is developed to increase the skill level and to update student's information record in school to be more efficient. Besides, it also provides student's information to the school administrator so that they can plan, develop, increase the student's academic performance and school co-curriculum. The main purpose of this system is to ease any information tasks regarding with student in school that have left the school, the attendance, the curriculum, school co-curriculum, and transferring from different classes within the school. Users has to insert student's lD number into the database for information retrieval. The development of this system will ensure the process of students information analysis in school according to their class, race, sex and religion.